Encounters with Kierkegaard : a life as seen by his contemporaries - Kirmmse, Bruce H. (Princeton University Press, 1996)
Encounters with Kierkegaard is a collection of every known eyewitness account of the great Danish thinker. Through the sharp observations of family members, friends and acquaintances, supporters and opponents, the life story of this elusive, remarkable figure comes into focus, offering a rare portrait of Kierkegaard the man. These accounts, ranging from the writings of Meir Aaron Goldschmidt, editor of The Corsair, to the recollections of Kierkegaard's fiancee, are organized around the major episodes of the philosopher's life. They enable us to glimpse, among many things, his spiritual and intellectual development, to get a sense of what it was like to be the object of his friendship or his wrath, and to examine various opinions about his relationship with his young fiancee.